Hemophilia A and Hemophilia B: Different Types of Diseases? - Santagostino, Elena; Fasulo, Maria Rosaria (Seminars in Thrombosis and Hemostasis, 2013)
Hemophilia A and B are traditionally considered clinically indistinguishable; however, differences in bleeding frequency, clinical scores, use of prophylaxis, and need for orthopedic surgery have been reported, suggesting that the bleeding tendency associated with factor IX deficiency may be less severe with consequent better outcomes in the long term.Hemophilia A and B show their own peculiar aspects, not only in terms of epidemiological and clinical features, including inhibitor incidence and associated symptoms, but also with respect to molecular defects. The type of factor VIII/IX mutation is a major determinant of the bleeding tendency as well as of the risk of inhibitor formation; thus, there is a biological plausibility behind the different clinical expression of these two forms of congenital hemophilia. The distinction of various bleeding phenotypes in hemophilia has considerable therapeutic implications; therefore, further research in this field is required to optimize treatment regimens.
Keywords: hemophilia B; hemophilia A; factor IX; factor VIII; genotype; phenotype; bleeding symptoms